One-step preparation of alpha-chlorostyrenes - Borate, Hanumant B.; Galkwad, Abaji G.; Maujan, Suleman R.; Sawargave, Sangmeshwer P.; Kalal, Kamalakar M. (Tetrahedron Letters, 2007)
alpha-Chlorostyrenes were prepared via a one-step method involving Friedel-Crafts reaction of various aromatic substrates with acid chlorides in the presence of a heterogeneous Si-Fe catalyst. (c) 2007 Elsevier Ltd. All rights reserved.

Oxidation of benzylic alcohols and sulfides over LaCoO3 and TBHP - Patil, Mahesh L.; Maujan, Suleman R.; Borate, Hanumant B.; Uphade, Balu S. (Arkivoc, 2007)
A simple and efficient methodology has been described for the selective oxidation of secondary benzylic alcohols to the corresponding ketones. In contrast, primary benzylic alcohols afforded dimethyl acetals.
Keywords: acetals; benzylic alcohols; Oxidation; perovskite LaCoO3

One-step synthesis of 4-alkyl-3-aryl-2,6-dicyanoanilines and their use in the synthesis of highly functionalized 2,3,5,6,7-and 2,3,4,5,7-substituted indoles - Sawargave, Sangmeshwer P.; Kudale, Ananada S.; Deore, Jaydeep V.; Bhosale, Dattatry S.; Divse, Jaisingh M.; Chavan, Subhash P.; Borate, Hanumant B. (Tetrahedron Letters, 2011)
A three-component, one-step method for the synthesis of 4-alkyl-3-aryl-2,6-dicyanoanilines involving reaction of alkyl aldehyde, malononitrile and aryl aldehyde in presence of morpholine is reported. Highly functionalized 2,3,5,6,7- and 2,3,4,5,7-substituted indoles were prepared from these dicyanoanilines by reaction with ethyl bromoacetate. These substituted dicyanoanilines and indoles have a potential to be converted into various other compounds taking advantage of various functional groups present in these molecules. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: aldehydes; Dicyanoanilines; indoles; Malononitrile

One-step method for the synthesis of aryl olefins from aryl aldehydes and aliphatic aldehydes - Borate, Hanumant B.; Gaikwad, Supriya H.; Kudale, Ananada S.; Chavan, Subhash P.; Pharande, Shrikant G.; Wagh, Vitthal D.; Sawant, Vikram S. (Tetrahedron Letters, 2013)
A conceptually new one-step reaction affording unexpected aryl olefinic product from aromatic aldehyde, aliphatic aldehyde and malononitrile in the presence of acetic acid-ammonium acetate under mild reaction conditions without using any metal catalyst is reported. This novel reaction was used to prepare a number of substituted aryl olefins including new molecules. (c) 2013 Elsevier Ltd. All rights reserved.
Keywords: Aliphatic aldehyde; Aromatic aldehyde; Aryl olefin; Dicyanoaniline; Malononitrile